2015
DOI: 10.4236/nr.2015.67044
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Yield and Nutrients Content in Tomato by Vermicompost Application under Greenhouse Conditions

Abstract: Optimizing yield and nutrients content in crop production is the high time demand of arable farming. Vermicompost furnishes one of the most promising alternatives to costly chemical fertilizer. Therefore, a greenhouse experiment was conducted at NARC, Islamabad, to investigate the effect of different levels of vermicompost [having C/N=15/1 and 14 Plant Growth Promoting Rhizobacteria (PGPR)] on growth, yield and nutrients content in hybrid tomato (National Tunnel Tomato-04-08) under greenhouse conditions during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…A Similar work was done by Hyder et al (2015) who confirmed highest number of fruit (97) and diameter of the fruit (6.75 cm) in tomato plant due to the application of vermicompost (2 t/ha). The results are in conformity with Joshi et al (2016), that application of T 2 -RDF (20-40-0 NPK kg ha -1 ) recorded significantly higher number of pods plant -1 (79.60) and number of seeds pod -1 (13.45) in cowpea.…”
Section: Yield Parameters (Fig 1)supporting
confidence: 73%
“…A Similar work was done by Hyder et al (2015) who confirmed highest number of fruit (97) and diameter of the fruit (6.75 cm) in tomato plant due to the application of vermicompost (2 t/ha). The results are in conformity with Joshi et al (2016), that application of T 2 -RDF (20-40-0 NPK kg ha -1 ) recorded significantly higher number of pods plant -1 (79.60) and number of seeds pod -1 (13.45) in cowpea.…”
Section: Yield Parameters (Fig 1)supporting
confidence: 73%
“…The amount of dry matter produced also gave results parallel to the increase in wet weight. Several researchers have also reported that [11,12,13].vermicompot and phosphorus applications reported that the increase in plant yield. Leaf N and grain N concentrations increased as plant growth increased the amount of N (exploited nitrogen) removed from the soil.…”
Section: Resultsmentioning
confidence: 96%